IMPLEMENTASI NEW PUBLIC MANAGEMENT (NPM) DALAM PELAYANAN PUBLIK DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA MAKASSAR - Hendrawati Hamid (Jurnal Pallangga Praja (JPP), 2022)
The purpose of this study was to analyze the implementation of the seven characteristics of NPM in theMakassar City Investment and one stop service (dPMPTsP). NPM is a reform in public managementas an effort to further improve the quality of services to the community, has seven characteristics in itsimplementation, namely: professional management in the public sector, has performance standards andperformance measures, emphasizes more on controlling output and outcomes, division of work units,the existence of competition in the public sector, applying the private sector management model to thepublic sector, emphasizing savings in the use of resources. Using a qualitative approach with the type ofevaluation research, namely examining the implementation of public service reform. Research informantsare structural officials of echelon II, III and IV, service operational staff, and the community. Research datawere collected through in-depth interviews, observations, and documentation related to policies. The resultsshow that of the seven characteristics of NPM, which have been implemented properly, namely professionalmanagement, the existence of performance standards and performance measures, the division of work units,the existence of competition in the public sector. The characteristics that still need to be taken seriously andaddressed are the emphasis on controlling output and outcomes, applying the private sector managementmodel to the public sector, emphasizing savings in the use of resources.